Intratracheal instillation of keratinocyte growth factor decreases hyperoxia-induced mortality in rats. - Panos, R J (1995)
Alveolar type II cell proliferation occurs after many forms of lung injury and is thought to play a critical role in alveolar epithelial repair. Keratinocyte growth factor/fibroblast growth factor 7 (KGF) has been shown to promote alveolar type II cell growth in primary culture and alveolar epithelial hyperplasia in vivo. In this study, we used immunohistochemical analysis to determine the intrapulmonary distribution and cellular localization of recombinant human KGF (rhKGF) instilled into the trachea of rats. 6 h after administration, immunoreactive KGF was observed within the lung parenchyma and along alveolar epithelial cell membranes. By 18-24 h, KGF was detected intracellularly in alveolar epithelial cells and intraalveolar macrophages. Immunoreactive KGF was not demonstrable 48 h after delivery or in lung sections from PBS-treated animals. Intratracheal instillation of 5 mg/kg rhKGF stimulated a marked, time-dependent increase in the alveolar type II cell specific labeling index to a maximum level of 33 +/- 3% 48 h after rhKGF administration compared with 1.3 +/- 0.3% after PBS instillation. In addition, this increase in type II cell proliferation in vivo was documented by flow cytometric analysis of isolated type II cells which revealed a nearly fivefold increase in the proportion of cells traversing through the S and G2/M phases of the cell cycle. To test the hypothesis that KGFs effects on type II cells in vivo might affect the response to lung injury, rats were treated with rhKGF and exposed to hyperoxia. Animals that received 1 or 5 mg/kg rhKGF exhibited dramatically reduced mortality (P < 0.001, for both doses). Survival for animals treated with 0.1 mg/kg rhKGF was not significantly different from either untreated rats or animals treated with heat-denatured rhKGF. The lungs of rhKGF-treated animals that survived hyperoxia exposure had minimal hemorrhage and no exudate within the intraalveolar space. These experiments established that intratracheal administration of rhKGF stimulated alveolar type II cell proliferation in vivo and reduced hyperoxia-induced lung injury in rats. Directed delivery of KGF to the lungs may provide a therapeutic strategy to preserve or restore the alveolar epithelium during exposure to hyperoxia or other injurious agents.